State of the Art and Future Perspectives in Smart and Sustainable Urban Development - Yigitcanlar, Tan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contributes to the conceptual and practical knowledge pools in order to improve the research and practice on smart and sustainable urban development by presenting an informed understanding of the subject to scholars, policymakers, and practitioners. This book presents contributions-in the form of research articles, literature reviews, case reports, and short communications-offering insights into the smart and sustainable urban development by conducting in-depth conceptual debates, detailed case study descriptions, thorough empirical investigations, systematic literature reviews, or forecasting analyses. This way, the book forms a repository of relevant information, material, and knowledge to support research, policymaking, practice, and the transferability of experiences to address urbanization and other planetary challenges.